KARYA SENI PATUNG SIMBOLIK DALAM UNGKAPAN PERDAMAIAN - Timbangunusa Tumimbang (Universitas Trisakti, 2015)
AbstractArtwork is the power of symbol which is defining a power and spirit of the life;can be listened to, can be digested, due to the form of work is a manifestation ofobservation, contemplation, and final outcome from spiritual dialogue of thewriter; after watching, listening, feeling and contemplating what ever volatilein the soul. The power of work force is a author's soul introducory whichattached on the work; so that the work can interact and alive between all thatbreathes. The nature-environment along with the creatures which exist inaroungd is a bestfriend who told and retold. The humanity is similarity thatbind to be expressed in the form of work.In this matter, the humanity is a appealing “desideratum humanum” ofessential longing and humane. Art working is an effort in structuring idea andmind in the form of work which is named “the artist's dream”, so that canelaborate totally the form and the meaning. The quality of the artowork can beseen from the quality of concept and idea along with the function of the artworktoward human life, seen from side of value offered by the artwork and therelevancy for the improvement of culture and life's achievement and the valueswhich should be integrated by the human self.AbstrakKarya seni adalah sebuah kekuatan simbol yang memaknai kekuatandan semangat dalam hidup itu; dapat disimak, dapat dicerna, karenabentuk karya adalah wujud dari pengamatan, perenungan, dan hasilakhir dari dialog batin penulis; setelah melihat, mendengar, merasakandan merenungkan apa yang pernah bergejolak dalam jiwa ini. Kekuatanmakna karya adalah pengantar jiwa penulis yang melekat pada karyaitu; sehingga karya dapat berdialog dan hidup di antara semua yangbernafas. Alam-lingkungan serta mahluk-mahluk yang ada disekitarnya, adalah sahabat yang berceritera dan di ceriterakan. Halkemanusiaan adalah kesamaan yang mengikat untuk diekspresikan kedalam bentuk karya.Dalam hal ini, kemanusiaan merupakan seruan “desideratum humanum” menstrukturkan gagasan-gagasan dan pemikiran ke dalam wujudkarya yang disebut “mimpinya seniman,” sehingga dapat menguraikanbentuk dan pemaknaannya secara total. Bobot karya seni di lihat daribobot konsep dan gagasan serta fungsi karya itu terhadap kehidupanmanusia, di lihat dari sudut nilai yang ditawarkan karya danrelevaansinya bagi perkembangan kebudayaan dan cita-cita kehidupandan nilai-nilai yang hendak ditegakkan manusia itu sendiri.